LOCL-11 EGFR-MUTATED NON-SMALL CELL LUNG CANCER (NSCLC) LEPTOMENINGEAL DISEASE (LMD) IN A LARGE STEREOTACTIC RADIOSURGERY PATIENT COHORT: INCIDENCE AND OUTCOME. (5th August 2022) - Mullen, Reed; Donahue, Bernadine; Alzate, Juan; Silverman, Joshua; Berger, Assaf; Bernstein, Kenneth; Kondziolka, Douglas
Abstract: AIM: Patients with EGFR-mutated NSCLC brain metastases (BM) treated with targeted agents +/- radiosurgery (SRS) have increasing life expectancies. Systemic treatment may become less effective in preventing CNS progression as survival is prolonged. We sought to identify subsequent LMD in patients with EGFR-mutated NSCLC treated initially with SRS for BM and describe the associated features, treatment, and outcome. METHODS: Review of our prospective Gamma Knife registry identified 177 patients with EGFR-mutated NSCLC between 2005 and 2021 treated with SRS. The EMR was queried for development of LMD, and type of LMD was recorded (focal/nodular or diffuse). RESULTS: 38 (21%) of the 177 patients developed LMD at a median of 10 months (range 1-25 IQR) following SRS. 27 (71%) of these were on tyrosine kinase inhibitors (TKI) at time of LMD diagnosis. Median overall survival (OS) from initial SRS for the entire cohort was 21 months (18-27 95%CI). Median OS after LMD diagnosis was 5 months (2-32 95%CI). LMD was diagnosed radiographically in 35 patients (92%); 20 patients had diffuse, 15 had focal/nodular, and 3 had positive CSF cytology. 26 (68%) had systemic progression synchronously with LMD. 33 (87%) had treatment for LMD including 19 with whole brain radiation therapy, 16 with the addition of or increased dosing of TKI, 6 with SRS for nodular disease, and 9 with intraventricular chemotherapy. The one- and two-year survival rates following the diagnosis of LMD was 21% and 3%, respectively. CONCLUSION: LMD developed in a substantial subset of our patients, and despite the use of a variety of salvage therapies, survival was poor. Investigation to identify factors correlating with the development of LMD and those related to outcome are ongoing. The development of LMD on TKI in several of our patients supports efforts to pursue development of therapeutic agents with long-lasting CNS efficacy.